Using dried blood spots to quantitatively detect anti-SARS-CoV-2 IgG antibodies by ELISA: a validation study - Ylade, Michelle; Aziz, Asma Binte; Daag, Jedas Veronica; Crisostomo, Maria Vinna; Agrupis, Kristal-An; Maronilla, Maria Angela; Hong, Chloe Sye Lim; Kim, Hwa Young; Njau, Irene; Lopez, March Helena Jane; Deen, Jacqueline; Kim, Deok Ryun; et al. (The American journal of tropical medicine and hygiene, 2024)
ABSTRACT. SARS-CoV-2 serological testing is useful to determine seroprevalence, epidemiological trends, and the extent of transmission. The collection and transport of serum samples can be logistically challenging, especially in remote underserved areas. Dried blood spots (DBSs) would allow easier sample collection and logistical handling compared with standard serum collection, particularly for extensive and repeated SARS-CoV-2 serosurveys. We evaluated the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the IgG ELISA (Wantai, Beijing, China) using DBSs against sera for the quantitative detection of SARS-CoV-2 IgG antibody. The IgG ELISA was used to test paired sera and DBSs obtained from individuals with recent virologically confirmed COVID-19 illness and banked paired sera and DBSs collected before the COVID-19 pandemic. We found that 100/100 (100%) seropositive samples were positive using DBSs, and 193/194 (99%) seronegative samples were negative using DBSs. Compared with sera, the DBS method had a 100% sensitivity, 99% specificity, 99% PPV, and 100% NPV. Use of DBSs for SARS-CoV-2 household or population serosurveys may be considered in situations with limitations in sample collection, shipment, and storage.
Gesehen am 03.03.2025